Creating a lean culture : tools to sustain lean conversions - Mann, David, 1947- (CRC Press, 2015)
"The new edition of this Shingo Prize-winning bestseller explains how to implement a Lean transformation that works by developing a culture that builds success from the top down and the bottom up at the same time. This edition provides expanded coverage of executive responsibilities, 20 new case studies, and new examples from the healthcare and process industries. A must-read for any leader undergoing or considering a Lean transformation, this edition also includes expanded coverage of Lean management applications in complex cross functional value stream process improvement projects"--Resumé vydavatele
Keywords: podnikový management; výrobní management; organizace podniku; výkonnost podniku; organizační změna; organizační chování; kultura organizace; industrial management; production management; industrial organization; industrial productivity; organizational change; organizational behavior; corporate culture; štíhlá výroba -- lean management; monografie; monographs